Konseling Indigenous Berbasis Tata Nilai Budaya Lampung “Piil Pesenggiri” Dalam Pembentukan Perilaku Disiplin Siswa - Sari, Permata; Bulantika, Siti Zahra (Jurusan Bimbingan dan Konseling Islam, 2019)
The task of education provides a disciplined learning process for individuals. The issue of discipline is like a frightening specter for education providers and students. This study aims to formulate indigenous counseling od piil pesenggiri value based. Especially, the study aims to analyze the significance in piil pesenggiri to create the student's discipline. Piil pesenggiri has four aspects in managing people life: nemui nyimah, nengah nyappur, sakai sabaiyan, and bejuluk adek. By understanding those, people learn to live in that rule and norm, so the counsellor can accompany counselee to face the problem of disciplines